EFFECTS OF LATE QUATERNARY AND CONTEMPORARY CLIMATES ON ECOREGIONAL PLANT DIVERSITY ACROSS DIFFERENT BIOMES - Chun-Jing Wang; Zhi-Xiang Zhang; Yong-Kun Zhang1 (Journal of Animal and Plant Sciences, 2020)
Large-scale patterns of plant diversity and their determinants are central issues in macroecology and biodiversity conservation. Previous studies have shown that late Quaternary and contemporary climates can affect plant diversity at large scale. The main objective of our study was to explore the effects of late Quaternary and contemporary climates on ecoregional plant diversity (EPD). Here, we used global ecoregions to examine characteristic and geographically distinct features of plant diversity and quantified the joint and independent explanatory power of late Quaternary and contemporary climates to account for EPD across different biomes. Then, we tested environmental mean and heterogeneity hypotheses and found that both late Quaternary and contemporary climates (temperature and precipitation) can affect plant diversity at ecoregional scales. Furthermore, environmental heterogeneity (i.e., the heterogeneity of late Quaternary and contemporary climates) may have stronger explanatory power than environmental mean for EPD. However, climatic effects on EPD may depend on biome variation. The effects of late Quaternary and contemporary climates on EPD can persist widely in forest biomes and Temperate Grasslands, Savannas & Shrublands. The results of the current study inform the prediction of plant diversity under future climate change, and support long-term monitoring of plant diversity at ecoregional scales.
Keywords: current climate; ecoregion; forest biome; globe; historical climate; plant richness